Perhitungan Efisiensi Hydraulic Pumping Unit (HPU) pada Sumur yang Menggunakan Working Barrel Tipe Tubing Heavy Wall Barrel Mechanical PT. Pertamina Ep Cepu Regional 4 Zona 11 Cepu Field - Winarto, Winarto; Kamid, Abdul; Ramadhan, Ardi (Dinasti Research, 2025)
This final project report aims to calculate the maximum flow rate capability based on the IPR curve to determine the comparison between fluid types based on PwF, after which the volumetric efficiency calculation is carried out on the installed HPU pump to find out whether the volumetric efficiency is below 60% - 80%, if the volumetric efficiency is below the target then optimization is carried out on the HPU pump. To carry out this final project, a preliminary study was carried out by reviewing information both in literature from the company and interviews, and field observations. Furthermore, data collection was carried out through interviews and field observations for data acquisition. After knowing and obtaining data, data processing is carried out to study related to the initial objectives of this final project. After data processing, it is known that the evaluation results before optimization that volumetric efficiency is 42.816% with pressure well flowing conditions of 273,859 psi. This of course has been outside the provisions of a company where the company has a volumetric efficiency target of 80%. To increase volumetric efficiency, pump intake calculations are carried out to determine the optimal parameters of stroke length and SPM under PwF conditions obtained from the relationship curve of N and S values to Q. After using the optimal parameters from the N and S value relationship curve results, the volumetric efficiency increased to 85.751% with a pump displacement of 377,838 bbl/day which is not much different from the gross Q of 324 bfpd, so the objectives of the final project have been achieved.